Theoretical determination of biophysical parameters for optimising neural cells' three-dimensional structures cryopreservation - Sukach, Oleksandr; Kovalenko, Ihor; Vsevolodska, Svitlana; Ochenashko, Olga; Kovalenko, Svitlana (Problems of Cryobiology and Cryomedicine, 2025)
Using physical and mathematical modelling of the mass transfer processes of water and Me2SO, the values of the relative osmotically inactive volume for aggregates and spheroids of neural cells from newborn rats were determined. The evaluated parameters for aggregates and spheroids are 0.689 and 0.644, respectively. The study also presents theoretically calculated changes over time in the normalized osmotic pressure of Me2SO and the concentration of salt ions within spheroids and aggregates. From the dynamic curves of change in relative volume for aggregates and spheroids, the filtration coefficients for water and permeability for Me2SO were determined. It was found that aggregates, as less densely packed structures than spheroids, were characterised by higher permeability coefficients for water and Me2SO, particularly at 5 °C. At this temperature, 119 s is required for 95% saturation of aggregate cells with 10% Me2SO and 157 s for spheroid. This means that at a temperature of 5 °C, the equilibration time with the cryoprotectant Me2SO is 25% longer for spheroids than for aggregates. The obtained results indicate that spheroids as a more integral structure characterised by dense cell-cell and cell-extracellular matrix interactions, are more osmotically active compared to aggregates. These findings can be used to develop the optimal methods for cryopreservation of neural cell aggregates and spheroids. Probl Cryobiol Cryomed. 2025; 35(2): 76–84